2014
DOI: 10.1039/c4rp00105b
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the topic-specific nature of pedagogical content knowledge in teaching electrochemical cells and nuclear reactions

Abstract: The purpose of this study was to examine experienced chemistry teachers' pedagogical content knowledge (PCK) for two different topics in chemistry to better understand how PCK is specific to topic, including whether all components of PCK are topic-specific and to what degree. To explore the topic-specific nature of PCK, we examined two experienced teachers' PCK using a case study methodology. Multiple data collection strategies were used, including a card-sorting activity, Content Representation (CoRe), semi-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 42 publications
6
35
2
4
Order By: Relevance
“…Aydin, Friedrichsen, Boz and Hanuscin examined experienced chemistry teachers' pedagogical content knowledge (PCK) for two different topics in chemistry to better understand how PCK is specific to topic, including whether all components of PCK are topic-specific and to what degree. [46] The results revealed that the teachers used more content-based and 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 teacher-centered instruction to teach EC, whereas their instruction was less teacher-centered, and included Science-Technology-Society-Environment (STSE) discussions and implicit Nature of Science (NOS) instruction to teach nuclear reactions.…”
Section: Teacher Educationmentioning
confidence: 99%
“…Aydin, Friedrichsen, Boz and Hanuscin examined experienced chemistry teachers' pedagogical content knowledge (PCK) for two different topics in chemistry to better understand how PCK is specific to topic, including whether all components of PCK are topic-specific and to what degree. [46] The results revealed that the teachers used more content-based and 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 teacher-centered instruction to teach EC, whereas their instruction was less teacher-centered, and included Science-Technology-Society-Environment (STSE) discussions and implicit Nature of Science (NOS) instruction to teach nuclear reactions.…”
Section: Teacher Educationmentioning
confidence: 99%
“…content into effective teaching, an idea based on the observation that knowing the content is not enough to be able to teach and help students learn the content. Throughout the literature, multiple models for PCK have been described and used in a variety of contexts to frame research studies that focused on characterizing PCK and supporting instructors' development of PCK (72); many of these types of studies exist in chemistry education (73)(74)(75)(76)(77)(78)(79)(80)(81). More recently, an updated model of PCK has been presented, called the refined consensus model of PCK (82).…”
Section: Pedagogical Content Knowledgementioning
confidence: 99%
“…de eklenmesine karar verilmiştir. Aktiviteler hazırlanırken ilgili literatür çalışmaları (Friedrichsen ve Dana, 2003;Aydın, 2012) da göz önüne alınmış ve esas uygulama öncesi aktiviteler PAB alanında çalışmaları olan fen eğitimcisi iki yardımcı doçent ve bir profesöre gönderilmiş, uzman görüşü alınarak ardından pilot uygulama yapılmıştır. Hazırlanan aktiviteler bu araştırma kapsamına giren üç üniteye yönelik yazılmış olup, ilk uygulama birinci ünite bitiminde ikinci uygulama ise son ünitenin bitiminde yapılmıştır.…”
Section: Kart Gruplama Aktivitesinin Geliştirilmesi Ve Uygulanmasıunclassified
“…Bu bileşenler Friedrichsen ve Dana (2002) Fene yönelik oryantasyon bilgisini oluşturan farklı bileşenler Magnusson, Krajcik ve Borko (1999) tarafından belirtilmiştir ancak fen öğretimi oryantasyonu incelemeleri temelde sınıf içi gözlemlere ve araştırmacı yorumuna bağlı olup sadece görüşmelere dayandırılamaz (Friedrichsen, 2002). Yeni değerlendirilmeye başlanan, fene yönelik oryantasyon bilgisi incelemelerine bakıldığında yaygın bir kullanım olarak kart gruplama aktivitelerinin karşımıza çıktığı görülmektedir (Hewson ve Hewson, 1989;Friedrichsen ve Dana, 2003;Aydın, 2012). İlk kart gruplama aktivitesi (Hewson ve Hewson, 1989) incelendiğinde öğretmen oryantasyonlarının gruplandırılmadığı ve görüşmelere ağırlık verildiği görülmektedir.…”
Section: Introductionunclassified
See 1 more Smart Citation